Open access for community partners, impactful outputs for scholars: Leveraging scholarly communication movements to enhance reciprocity in community based research - Olivia Ivey; Rachel Borchardt (Michigan Journal of Community Service Learning)
Many corners of the academy are actively working to build bridges between research in the ivory tower to outcomes and needs in the community. Our study seeks to unify two such efforts – community-based/service-learning research and open access scholarly communication. Open access is an implicit value in community-based and service-learning research, and is part of the symbiotic relationship value, but has not been explicitly discussed, framed, or embraced as a value or goal. We explore existing literature on the desire for research-informed practices from community members and practitioners, the current state of open informational practices from scholarly publications dedicated to work happening in community spaces, and make recommendations for good practices for editors, publishers, researchers, and institutions looking to link the work of scholars to the needs of the community and evaluate impact.